Pengaruh Model Pembelajaran Kolaboratif Terhadap Hasil Belajar Matematika Dengan Mengontrol Bakat Numerik Peserta Didik - I Wayan E. Mahendra; I Gusti Agung N. T. Jayantika; Ni Gusti P. V. Mintarti (JOURNAL OF SONGKE MATH, 2018)
The main purpose of this study is to determine whether there is a difference in the model of collaborative learning on mathematics learning outcomes by controlling the numerical talents of learners. This type of research is quasi eksperiment with non equivalent control group design. The sample in this study consisted of two classes namely class X AP 1 as experiment class and class X AP 3 as control class with many students of each class were 39 and 38 students taken with sample random sampling technique. Data were analyzed using one-way t-test and ANAKOVA. Based on the results of hypothesis testing results obtained, there is a significant difference in the learning outcomes of learners who follow the learning model of collaborative learning with the learning outcomes of learners who follow the conventional learning model with the value of t-test. after controlling to student's numerical talent there is difference of significant result of learning of mathematics among learners which follow model of collaborative learning with learners result of learning that follow conventional learning model. So there is an influence of collaborative learning model on mathematics learning outcomes by controlling the numerical talents of learners.